Uma visita de Natal no rastro dos aviões franceses - François Weigel (Confins)
On May 13, 1930, Jean Mermoz landed his seaplane on the banks of the Potengi River in the city of Natal. He thus made the first commercial flight across the South Atlantic, between São Luís (Senegal) and Natal, allowing a considerable time saving for sending mail on the line established by Aéropostale (before 1927, by Latécoère and, from 1933, by Air France). This flight certainly represents the apogee of the line between Europe and South America, concretizing the central place that Natal occupied in the French air system during the 1920s and 1930s, at the time of the pioneers of commercial aviation. This article records the French company's presence in the region of Rio Grande do Norte and the Fernando de Noronha archipelago (in Pernambuco), assessing the historical impact of this commercial adventure on this territory and delimiting its marks and traces in the present day.